2001
DOI: 10.1159/000052636
|View full text |Cite
|
Sign up to set email alerts
|

Increased Expression of Glutathione S- Transferase in Renal Proximal Tubules in the Early Stages of Diabetes: A Study of Type-2 Diabetes in the Akita Mouse Model

Abstract: Background/Aim: The objective of this study was to examine whether the gene expression profile in the kidney is modified by hyperglycemia in the early stage of diabetes. Methods: We analyzed the expression of kidney mRNAs using cDNA array membranes including 588 genes in the kidney of the Akita mouse, a model of type-2 diabetes, after exposure to hyperglycemia for a moderate length of time, but before the manifestation of diabetic glomerulosclerosis. Western blot analysis and immunohistochemical studies were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
13
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 17 publications
7
13
0
1
Order By: Relevance
“…Albuminuria is not a prominent feature in diabetic C57BL/6 Ins2 Akita mice (10,37). In our study, nonmutagenized C57BL/6 Ins2 Akita mice exhibited an average AER of 36 Ϯ 14 g/24 h, in agreement with a previous report (38). Among G1 progeny that were generated from mating between ENU-mutagenized male and female C57BL/6 Ins2 Akita heterozygotes, we identified six Ins2…”
Section: Discussionsupporting
confidence: 92%
“…Albuminuria is not a prominent feature in diabetic C57BL/6 Ins2 Akita mice (10,37). In our study, nonmutagenized C57BL/6 Ins2 Akita mice exhibited an average AER of 36 Ϯ 14 g/24 h, in agreement with a previous report (38). Among G1 progeny that were generated from mating between ENU-mutagenized male and female C57BL/6 Ins2 Akita heterozygotes, we identified six Ins2…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, as described by others in previous studies, we observed mesangial expansion as sign of early diabetic glomerular alterations by both light and electron microscopic examination. 10,17,32,33 In addition, an increase of urinary albumin excretion was noted, indicative of some abnormality of glomerular permselectivity, but as in other studies in Ins2 ϩ/Ϫ mice, the increase in albumin excretion was mild. 16,17,32,34 Our BASIC RESEARCH www.jasn.org study shows that the glomerular abnormalities observed in Ins2 ϩ/Ϫ mice are enhanced in these mice when they lack A1AR.…”
Section: Discussionsupporting
confidence: 67%
“…As seen with other models of DN in the C57BL/6J strain, albuminuria is not a prominent feature (10.23 Ϯ 2.73 g/24 h in diabetic mice versus 13.9 Ϯ 8.8 g/24 h in controls) (89). Renal immunopathologic studies show significant deposition of IgA in the glomeruli of Akita mice (88); however, given the association of IgA deposition in glomeruli of up to 20% of humans with diabetes (90) and rat models of diabetes, the significance of these findings is uncertain (91)(92)(93).…”
Section: Insulin-2 Akitasupporting
confidence: 55%